Reconciliation In The Iraqi Code Of Criminal Procedure In Force - Jawad Mahdi, Ayad (Opción, 2019)
Reconciliation is one of the most important issues of criminal justice. Accord- ingly, the Iraqi legislator regulated the provisions of reconciliation between the conditions and its effects in Chapter V of Part III of Book III of Articles (194-198) of the Code of Criminal Procedure No. 23 of 1971 as amended. The reasons that led the Iraqi legislator to accept and accept the principle of rec- onciliation or conciliation in the criminal case are the serious desire to end and resolve the conflict in specific crimes in order to spread peace between the parties to the criminal case and to deter taking revenge and end it. The frame- work of not blocking reconciliation in some minor crimes itself and avoiding the complications of conviction and punishment for the crime. Although the legislator defined the methods for ending the criminal case as stated in Article (300) of the Code of Criminal Procedure in force, it is a first part as it is said that (peace is the master of judgments), therefore, reconciliation is a special reason for stopping the progress of the criminal case and its expiration The ef- fect of the conciliation decision is similar to the acquittal. Thus, it is clear that the appointment of the peace by the legislator is acceptable and justified, but what is taken and that it has expanded in some cases, as it included crimes in which it was better not to accept reconciliation, such as crimes of threat, abuse and sabotage of funds that may be vetoed by the judiciary at the discretion of the crimes He did not approve the judgment of reconciliation or reconciliation for reasons related to the duration of the negative sentence of freedom.